Effect of Inflation, Economic Growth, Leverage on Profit Increase: The Moderating Role of Company Size in Fashion Industry the IDX - Siti Aisyah Al Fatih; Fahmi Natigor; Yeni Absah (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to examine and analyze the influence of inflation, economic growth, and leverage on profit growth, with firm size as a moderating variable. The research objects are fashion retail companies listed on the Indonesia Stock Exchange during the 2017–2024 period. This study uses a quantitative descriptive approach. The sampling technique used is purposive sampling based on certain criteria. Based on this method, six companies were obtained as research samples with a total of 48 observations. The data used are secondary data sourced from annual financial reports and macroeconomic data. All data were then analyzed using eViews software version 12. The results show that inflation has a negative effect on profit growth in fashion retail companies. Meanwhile, economic growth and leverage have been shown to have a significant effect on profit growth. In addition, firm size is able to moderate the relationship between inflation, economic growth, and leverage on profit growth. These findings indicate that internal company characteristics, especially firm size, play an important role in strengthening or weakening the influence of macroeconomic and financial factors on profit performance.